Semantic prosody of [pendidikan/education] from Khaled Nordin's perspective: An analysis of speech texts based on Corpus Linguistic Methodology - Isam, Hishamudin; Mohd Zain, Mohd Izani; Abd Mutalib, Mashetoh; Haron, Rohaidah (Elsevier Ltd., 2014)
Education generally is a planned initiative related to the teaching and learning process to produce learners who are active in developing their potential to meet their own needs and society's.Synergistic process conducted ultimately aims to produce a positive output acceleration of human capital that has religious and spiritual strength, self-control, personality, intelligence, good characters and competent, dedicated to the challenges and needs of the 21st century.Armed with such commitment, Higher Education Minister, Datuk Seri Mohamed Khaled Nordin in his speeches often reveals the diversity of education issues in Malaysia particularly in relation to education at the tertiary level. Therefore, this study will describe the information that can be tapped from the use of [education] lexis in his speech texts through the analysis of semantic prosody based on corpus linguistics. A total of 20 speeches are selected at random from a collection of his speeches from 2009 to 2012 to be analyzed. Semantic prosody analysis results show most often Khaled Nordin highlights four (4) text information related to the main theme education namely strengthening the quality of higher education and its academicians, strengthening research and innovation development besides quality student development, and human capital employability. This situation would highlight the evidence that lexis in a language would be able to reveal text information that could be used to understand lexical meanings and values and could also enlighten the leadership identity of its users. The situation is thus able to prove that there are explicit and implicit links between the reality of the language usage and the social reality of its users.